1992
DOI: 10.1103/physreva.45.6123
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of stochastic pulsation in laser-plasma interaction by smoothing methods

Abstract: Smoothing of laser-plasma interaction by ISI, RPP, SSD, etc. was mainly directed to overcome lateral nonuniformity of irradiation. While these problems are in no way less important, we derived numerically the model of the Laue rippling and hydrorelaxation model for explanation of the measured temporal pulsation in the 10-to 40-ps range and how the smoothing schemes suppress these pulsations. The partial standing wave fields of the normally coherent laser-irradiated plasma corona is then suppressed by smoothing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
28
0

Year Published

1993
1993
2015
2015

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(31 citation statements)
references
References 19 publications
3
28
0
Order By: Relevance
“…The use of the complex refractive index changing spatially and temporally on the plasma temperature and density is correctly expressed in the second formulation by the rule that the real parts of the fields are to be used for the quadratic expressions of the laser field. In order to test our advanced version of the two-fluid hydrodynamic code, we computed the case of the same parameters as previously published (Hora and Aydin 1992) and confirmed identical results.…”
Section: Two-fluid Plasma Hydrodynamics Codesupporting
confidence: 55%
“…The use of the complex refractive index changing spatially and temporally on the plasma temperature and density is correctly expressed in the second formulation by the rule that the real parts of the fields are to be used for the quadratic expressions of the laser field. In order to test our advanced version of the two-fluid hydrodynamic code, we computed the case of the same parameters as previously published (Hora and Aydin 1992) and confirmed identical results.…”
Section: Two-fluid Plasma Hydrodynamics Codesupporting
confidence: 55%
“…The interaction of a short laser pulse with an inhomogeneous plasma layer was investigated with the use of the computation code of the advanced two-fluid plasma model [11,12]. This model is based on the nonthermalized direct electromagnetic interaction between the laser light and the fully ionized plasma.…”
Section: Two-fluid Hydrodynamic Modelmentioning
confidence: 99%
“…Since the iron was separated from the laser focus it was concluded that energetic electrons are synchronously produced with the maxima of the back-scattered light (Luther-Davies & Rode 1993). A general numerical treatment that follows the latter numerical observations can explain both the pulsation process and how to suppress it by broadband laser irradiation (section 4) (Hora & Aydin 1992). This is a kind of beam smoothing that was suggested as a possibility by Deng (1983) and before other smoothing techniques (random phase plate (Kato et al 1985) or short temporal coherence (Lehmberg & Obenschain 1983) were intuitively introduced.…”
Section: Introductionmentioning
confidence: 91%